2018
DOI: 10.1111/ctr.13273
|View full text |Cite
|
Sign up to set email alerts
|

Role of the oxidative stress index, myeloperoxidase, catalase activity for cardiac allograft vasculopathy in heart transplant recipients

Abstract: An increase in the serum level of OSI, MPO, and CAT was associated with CAV in HTRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In accordance with Kargin et al's report [ 4 ], we observed that in patients with angiographic evidence of CAV, the antioxidant mechanisms were exhausted, as evidenced by a significantly lower TAC level in patients with CAV than in those without CAV. Furthermore, we found increased secretion of ROS, identified by higher values of TOS and OSI in patients with CAV than in those without CAV.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In accordance with Kargin et al's report [ 4 ], we observed that in patients with angiographic evidence of CAV, the antioxidant mechanisms were exhausted, as evidenced by a significantly lower TAC level in patients with CAV than in those without CAV. Furthermore, we found increased secretion of ROS, identified by higher values of TOS and OSI in patients with CAV than in those without CAV.…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative-antioxidative balance disorders in the prooxidative direction cause a cascade of changes that lead to damage of the vascular endothelium, constituting the main point of CAV development. Permanent smoldering, low-grade vascular inflammation, and oxidative stress cause progressive endothelial damage in the coronary arteries, leading to CAV initiation and progression [ 4 , 5 , 7 ]. To minimize damage caused by ROS, the body uses enzymatic and nonenzymatic antioxidant systems that restore the proper oxidative-antioxidant balance [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidative as well as antioxidative pathways are involved in various immune and inflammatory reactions and may play a role in the development of transplant vasculopathy [3]. As for heart transplant recipients, an increase in oxidative stress and antioxidant enzyme activity was shown to be associated with development of cardiac allograft vasculopathy [4].…”
Section: Introductionmentioning
confidence: 99%